The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/biom9090468
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Selected Stilbenoid Derivatives in a Cellular Model System

Abstract: The stilbenoids, a group of naturally occurring phenolic compounds, are found in a variety of plants, including some berries that are used as food or for medicinal purposes. They are known to be beneficial for human health as anti-inflammatory, chemopreventive, and antioxidative agents. We have investigated a group of 19 stilbenoid substances in vitro using a cellular model of THP-1 macrophage-like cells and pyocyanin-induced oxidative stress to evaluate their antioxidant or pro-oxidant properties. Then we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…Structural Motif (26)(27)(28)(29)(30)(31)(32) Step 1: Starting dichlorotriazinyl benzene sulfonamide (1 mmol) was dissolved in 10 mL of DMF. One mmol of solid anhydrous potassium carbonate was added in small portions, and the mixture was stirred for 10 min.…”
Section: General Methods For Synthesis Of Trisubstituted Derivatives Omentioning
confidence: 99%
See 1 more Smart Citation
“…Structural Motif (26)(27)(28)(29)(30)(31)(32) Step 1: Starting dichlorotriazinyl benzene sulfonamide (1 mmol) was dissolved in 10 mL of DMF. One mmol of solid anhydrous potassium carbonate was added in small portions, and the mixture was stirred for 10 min.…”
Section: General Methods For Synthesis Of Trisubstituted Derivatives Omentioning
confidence: 99%
“…They might have an effect on the production of catalase, heme oxygenase-1, and glutathione peroxidase enzymes. Depending on their molecular structure, they can produce antioxidative but also pro-oxidative effects [31]. Resveratrol (stilbene analogue; see Figure 1f) is an example of phenolic antioxidant, which serves in medicine as an adjuvant treatment of cardiovascular diseases, metabolic syndrome, type 2 diabetes, and inflammatory diseases [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, including the research with 19 stilbenoids, on human monocytic THP-1 cell line (THP1-XBlue™-MD2-CD14) and human hepatoma cell line (HepG2), showed that ISO has mild antioxidant activity compared to piceatannol. Interestingly, ISO activated the increased expression of the nuclear factor erythroid 2-related factor 2 (Nrf2), the transcription factor that controls the expression of genes encoding cytoprotective enzymes and protein [55].…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 99%
“…Stilbenoids and related compounds are produced by plants for antifungal and antibacterial purposes. Nineteen stilbenoid derivatives were tested in a cellular model system, some of which exhibited antioxidant properties while others were pro-oxidative (Treml et al, 2019). Among these, resveratrol was found to have direct scavenging effect on reactive oxygen species (ROS) (Akinwumi et al, 2018).…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…Stilbenoids have been of interest due to their antioxidant (Oh and Shahidi, 2017;Oh et al, 2019;Treml et al, 2019), anti-inflammatory (Leláková et al, 2019;Hošek et al, 2019), anticancer (Cuzick et al, 2015) cardioprotective (Zamora-Ros et al, 2012), anti-Alzheimer's (Moussa et al, 2017), and anti-diabetic (Banaszewska et al, 2016) activities. In addition, resveratrol, for example, has a higher lipophilicity compared to other phenolic compounds, which may lead to its better cell permeability (Neves et al, 2013).…”
Section: Introductionmentioning
confidence: 99%